CENTRAL POLITICS, GERMAN IMMIGRATION AND LITTLE PEOPLE AT THE NINETEENTH-ONIC BORDER. VALDIVIA, LA UNIÓN AND OSORNO (1840-1890) - Muñoz Sougarret, Jorge (Revista de Historia Social y de las Mentalidades, 2025)
For the historiography the south border of the  araucanía has suffered, during the second half  of the 19th century, a point unique of notable  inf lexion, the arrival of  german immigrants.  of equal way, the rest of the local population  has appeared in a background, often so much  as shackler or extra of the impulses developer of the colonists. Knowing the previous  thing, and without expecting to generate a  diametrical change, we have centred on this  work on such populations of natives, how they  were affected by the immigration and how  they faced the relating to the moment changes  that shook the foundations of his society.
Keywords: german immigration; austral chile; delinquency